Information technology, development, and social change - Patel, Fay. (New York : Routledge, 2012)
"The speed and cost effectiveness of new information technology has prompted many to view these innovations as a panacea for social and economic development. However, such a view flies in the face of continuing inequities in education, health, food, and infrastructure. This volume explores these issues - along with questions of access, privilege, literacy, training, and the environmental and health effects of information technologies in the developing world - arguing that a higher level of development does not always result from a higher level of technologization."--Provided by publisher.
pt. 1. Alternative perspectives on the diffusion of innovations andinternational development -- pt. 2. Innovative technology : impact on developing communities -- pt. 3. International development : critical perspectives on health,poverty, and environment.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Information technology; Economic development; Digital divide; Social change; Electronic books